PENGELOLAAN DANA PENSIUN SYARIAH MENGGUNAKAN AKAD MURABAHAH DI BANK SYARIAH MANDIRI - Khadijatul Musanna (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2023)
The goal of this study is to examine the mechanism of the murabaha contract as it is enforced in BSM and its applicability in the National Sharia Fatwa Council (DSN) of the Indonesian Ulema Council (MUI) No: 04/DSN - MUI/IV/2000 about General Provisions on Murabahah Contracts. The study technique employed is descriptive qualitative, with data gathering methods based on primary data acquired from Fatwa BSM and DSN-MUI official websites, as well as secondary data sourced from related articles and journals. The results of the research are that the mechanism for managing pension funds for murabahah contracts is very flexible, starting with the customer's will and BSM's approval, then BSM takes over from TASPEN and then the funds are disbursed. and the mechanism for changing the pension fund agreement has met the standardization of the DSN-MUI Fatwa Number 4 of 2000.